Short-Range Nonstationary Clutter Suppression for Airborne KA-STAP Radar in Complex Terrain Environment - Yuanyi Xiong; Wenchong Xie; Yongliang Wang; Wei Chen; Ming Hou (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Due to the range ambiguity effect and the complex terrain environment, the remote weak target of interest for nonsidelooking airborne radar is usually superimposed with the nonstationary and heterogeneous short-range strong clutter, so it is difficult for the traditional space–time adaptive processing (STAP) methods to achieve effective moving target detection. Therefore, the detection of the remote weak moving target in the heterogeneous and nonstationary clutter environment is one of the difficulties encountered by airborne radar. Through the analysis of airborne radar clutter characteristics, we have found that the short-range nonstationary clutter and the long-range ambiguous clutter do not overlap in Doppler domain, so the homogeneous training samples can be effectively selected through the digital terrain database. On this basis, the article establishes the refined grid dot level clutter signal model of airborne radar and proposes a three-dimensional STAP (3D-STAP) method based on the digital terrain database, namely the DTD-3D-STAP method. The method first accurately registers the airborne radar echo with the grid dots of the digital terrain database; next, the training samples are selected along the equal Doppler line based on prior knowledge; then, the training samples can be compensated through power compensation; and finally, the short-range nonstationary clutter is suppressed through 3D-STAP technology. On one hand, the proposed method ensures the homogeneity of the clutter spectrum and power of the training samples, and the sample can be detected through prior knowledge and power compensation. On the other hand, 3D-STAP technology is used to effectively suppress nonstationary clutter. Computer simulation and experimental results verify the effectiveness of the proposed method.